Das Wahr-Sagen des Marxismus: Foucault und Marx - Demirović, Alex (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2008)
In the first instance, Foucault seemed to be very far from Marx, speaking of Marx in terms of obsolescence, although important as a historical figure. But Foucault is situating his own work in the context and the set of problems of Marx’ theory. Thus Foucault’s work may be seen as an attempt of critical self: reflection on the claims for power of truth in Marxism. At least this leads Foucault to a conceptualization of power and social contradictions that disables him to acknowledge the radical emancipatolY thrust of Marx’ work.